Emphysema model in rats exposed to tobacco smoke. Morphometric and functional analysis - Reyna Sepúlveda, Francisco Javier; Caballero Mendoza, E.; Guzmán de la Garza, Francisco Javier; Fernández Garza, Nancy Esthela; Muñoz Maldonado, Gerardo Enrique; Ancer Rodríguez, Jesús (UANL. Facultad de Medicina, 2016)
Several models of chronic obstructive pulmonary disease (COPD) in mice have been developed; the most similar to the habit of smoking is the inhalation of the smoke in mice. The objective was to develop and implement an experimental model of COPD in mice through the passive inhalation of smoke and demonstrate the physiological changes on ventilatory function and its correlation with 3 emphysema quantification methods. Materials and methods: Twenty Wistar mice were included in an experimental and control group. The experimental group was exposed to tobacco smoke, and we performed several pulmonary functional tests and imaging techniques. Results: Pulmonary function tests showed the volume expiration in the first second (VEF1) differs significantly between groups (p < 0.001). Pulmonary compliance was reduced in the experimental group by 50% in comparison to the control group (male vs control p < 0.001). Morphometric analysis: 17% reduction in lung volume with a destructive index (DI) of 45%. The intersection test had a DI of 43%. The free point test showed a DI of 44%. Conclusions: The implementation of our model generated the presence of emphysema and alterations in the lung physiology in the experimental group. We demonstrated evidence of 90% with emphysema